Hubungan Usia dengan Kejadian Preeklamsia pada Ibu Hamil di RSUD Kabupaten Kediri Tahun 2018: The Relationship between Age and the Incidence of Preeclampsia in Pregnant Women at the Kediri District Hospital in 2018 - Ertiana, Dwi; Wulan, Suci Retno (Jurnal Kebidanan Midwiferia, 2019)
The objective of this study was to determine the relationship of age with the incidence of preeclampsia in pregnant women in Kediri District Hospital. The study was conducted on April 8 to April 25, 2019 in Kediri District Hospital using instruments in the form of document sheets, namely the patient's medical record. The research method used was an analytical survey with a retrospective cohort approach, with independent variables of age in pregnant women and dependent variables for the incidence of preeclampsia. The total population of 3,096 respondents with a Simple Random Sampling sampling technique obtained as many as 179 respondents. The results showed almost half of the respondents (32.4%) 58 respondents were at risk of age who suffered preeclampsia in pregnancy and a small proportion of respondents (14%) 25 respondents were of non-risk age who suffered preeclampsia in pregnancy. Analysis using Chi Square obtained p value = 0,000 <α 0,05, CC value = 0,376, CI value = 2,962 - 10,718 and OR = 5.6, so Ho was rejected and H1 was accepted means there was a relationship between age and the incidence of preeclampsia in pregnant women in Kediri District Hospital. Mothers with an age at risk of being prone to preeclampsia because of an oxidative increase so that the production of trophoblast apoptosis and necrotic debris also increases, this causes a systemic inflammatory reaction. To prevent the occurrence of preeclampsia in pregnant women can make early detection in pregnancy.